Metode Pembelajaran Al-Quran Bagi Anak Berkebutuhan Khusus Tunanetra - Marhaban Aqil Afif; Unik Hanifah Salsabila; Amar Syaifullah; David Hariadi (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2021)
The purpose of this research is to find out the methods and media used in the learning of the Quran for children with special needs of the visually impaired. The method used in this research is literature research which in conducting this research to obtain or collect compiling information using the help of internet applications to browse books, journals and other scientific works related to research topics. Then the data is summarized and focuses on the main thing only then arranged with the theme and pattern that has been determined. The result of the discussion in this study are that there are various methods of learning Al-Quran for children with special needs blind, including lecture methods, discussion methods, sorogan methods, bandongan methods, and drill methods. Learning media is needed to assist in the implementation of these methods. Some of media or tools used for learning the Quran for children with special needs blind, among others, the Quran braille, reglet and stylus, and Al-Quran audio. Learning the Quran in children with special needs visually impaired has the aim of making them become themselves skilled in understanding, reading, writing, studying or practicing the teachings of the content in the Quran.